If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 22 + -9x = 25 Reorder the terms: 22 + X + -9x = 25 Solving 22 + X + -9x = 25 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + X + -22 + -9x = 25 + -22 Reorder the terms: 22 + -22 + X + -9x = 25 + -22 Combine like terms: 22 + -22 = 0 0 + X + -9x = 25 + -22 X + -9x = 25 + -22 Combine like terms: 25 + -22 = 3 X + -9x = 3 Add '9x' to each side of the equation. X + -9x + 9x = 3 + 9x Combine like terms: -9x + 9x = 0 X + 0 = 3 + 9x X = 3 + 9x Simplifying X = 3 + 9x
| 2y+4=.166667 | | 4x(x-3)=1 | | (v^2+6v+8)(4v-4)=0 | | 9x+3+5x-2+11x-21=180 | | 4x(x-1.5)=1 | | 0.12h-0.6=-0.06 | | 4x-17+2x=25 | | 23+t=16 | | 4w-5=13 | | 2/3k=20 | | 5x^2-25x-34=0 | | 4*x+2*y=25 | | 14bc/49cd | | 7-3x=4+(y+7) | | -4x+7+7x=-20 | | -7=1/5a | | x+4-6x=-21 | | 12n+7-8n=54 | | 9w-48=-5(w+4) | | (-4x+5)-(6x+7)=0 | | 6(x+1)-3x=-9 | | -5a+2+6a=5-30 | | 5-x^2=3-x | | 2x-8/4=9 | | x^2+5x-43=7 | | -2(x-4)-12=16 | | -2(x+2)-8=10 | | 3a+6a=2a | | -5(5x+1)=45 | | 8-2(4y+12)=18 | | n-9= | | 3x*x-2=5x |